Aerospace series. Screw, pan head, Spiral Drive Recess, coarse tolerance normal shank, medium length thread, in alloy steel, cadmium plated. Classification: 1 100 MPa (at ambient temperature)/235 °C. (8th April 2022) - British Standards Institution,
No abstract available